Complication rate of uterine morcellation in laparoscopic supracervical hysterectomy: a retrospective cohort study. (April 2016) - Smits, Roos M.; De Kruif, Jan H.; Van Heteren, Cathelijne F.
Abstract: Background: Over the last decades minimally invasive surgical techniques are increasingly used to treat symptomatic leiomyomas, providing the patient decreased morbidity and more rapid return to daily activities. Morcellation is the fragmentation of a large mass into smaller pieces to make resection through port incisions possible. Over the last year there has been a discussion worldwide about the safety of morcellation. Objective: The aim of our study was to identify the complication rate of power morcellation at our institution. Study design: We performed a retrospective chart analysis of patients undergoing laparoscopic supracervical hysterectomy with morcellation. We compared the outcomes of patients undergoing laparoscopic supracervical hysterectomy with the use of power morcellation with a control group of women who underwent laparoscopic-assisted vaginal hysterectomy without morcellation. Women who underwent hysterectomy because of suspected malignancy were excluded. Results: A total of 358 patients underwent laparoscopic hysterectomy between 2004 and 2013; 186 laparoscopic supracervical hysterectomies and 172 laparoscopic-assisted vaginal hysterectomies. The main indication for laparoscopic supracervical hysterectomy was heavy menstrual bleeding and pelvic pressure or pain (94.5%). Baseline characteristics were not significantly different except for body mass index, with a mean of 25.7 in laparoscopic supracervical hysterectomy and 27.0 in laparoscopic-assisted vaginal hysterectomy. There was a significant greater uterine weight in the laparoscopic supracervical hysterectomy group (260 g vs. 202 g). The overall conversion rate was 5.3% ( n = 19), with no significant difference between the two groups and 79% of conversions being performed for strategic reasons. There was no statistical difference in intra-operative complication rate (2.1% vs. 1.2%). Pathology reports showed no unexpected malignancies. There was no statistical difference in the complication rate post-operatively (2.2% vs. 2.9%). The overall complication rate of laparoscopic supracervical hysterectomy was 4.3% ( n = 8). Need for reoperation after laparoscopic supracervical hysterectomy was necessary in 7 patients (3.8%), with cervical amputation being the most common type of reoperation ( n = 5). In the laparoscopic-assisted vaginal hysterectomy group there were significantly more adhesiolysis performed ( n = 4). Parasitic myomas were discovered in 1 patient two years after morcellation (0.5%). Conclusion: Our study showed no injuries directly related to morcellation. There were no unexpected malignancies morcellated and only one case of parasitic myomas (0.5%).